1st Virtual International Conference on Equality, Religious Harmony and Peace - Mohd Salleh, Hamzah; Nik Mohamed, Mohamad Haniki; Hassan, Rusni; Mumtaz Ali, Mohammad (2021)
An international conference organised by the Office of the Deputy Rector (Internationalisation and Global Networking) was successfully held for the first time, virtually on 18-19 November 2020 at the IIUM Gombak campus. The scope of the conference includes, but not limited to, religious diversity, gender dysphoria, civilization, racism, conflict resolution, terrorism, Islamophobia, gadgetism, global citizenship, good governance, and populism.